Dissemination of salt tolerant mustard varieties through frontline demonstrations approach for sustainable mustard production in Pali district of Rajasthan (Journal of Oilseed Brassica, 2026)
Front line demonstrations (FLDs) on mustard were laid down at 565 farmers’ fields to demonstrate production potential and economic benefits of improved production technologies comprising salinity tolerance varieties namely CS 52, CS 54, CS 56 and CS 58 in Pali district of arid zone of Rajasthan state during Rabi seasons from 2012-13 to 2017-18 in irrigated farming situation. The findings of the study revealed that the improved production technologies recorded an additional yield ranging from 3.6 to 7.9 q/ha with a mean of 5.5 q/ha. The per cent increase yield under improved production technologies ranged from 35.8 to 68.7 (CS 52), 34.3 to 57.9 (CS 54), 37.6 to 65.9 (CS 56) and 61.5 to 67.5 (CS 58) in respective years. The average extension gap, technology gap and technology index were 5.5q/ha, 6.5q/ha and 28.3 per cent, respectively in different salt tolerance varieties of mustard. The improved production technologies gave higher benefit cost ratio ranging from 2.4 to 3.6 with a mean of 2.6 as compared to local checks (1.9) being grown by farmers under locality. The results revealed that the maximum number of the respondents had medium level of knowledge and extent of adoption regarding recommended mustard production technology. The study reported lack of suitable salinity tolerance HYV as major constraints by beneficiaries at rank first followed by low technical knowledge. Thus the productivity of mustard per unit area could be increased by adopting feasible scientific and sustainable management practices with a suitable salinity tolerance variety